PENGARUH KECERDASAN EMOSIONAL, KECERDASAN SPIRITUAL, DAN KOMITMEN ORGANISASIONAL TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) (STUDI PADA DOSEN TETAP PERGURUAN TINGGI KEAGAMAAN ISLAM SWASTA ) - irhas irhas (Master of Management, Mataram University, 2017)
This research aims at finding and the influence of : (1) Emotional Quotient on OCB, (2) Spiritual Quotient on OCB, and (3) Organizational Commitment on OCB. This research is causal associative research which uses questionnaire as the instrument of Data Collection. The Population of this research are 119 Permanent Lecturers of Private Islamic Higher Education in East Lombok West Nusa Tenggara Indonesia. Questionnaire was used to collect data. The collected data were then analyzed with Linear Multiple Regression. The result shows that: (1) Emotional Quotient has positive , but insignificant effect on OCB, (2) Spiritual Quotient has positive and significant effect on OCB, and (3) Organizational commitment has positive and significant effect on OCB.Keywords: Organizational Citizenship Behavior, Emotional Quotient, Spiritual Quotient, and Organizational Commitment.